3D Printed Personalized Nerve Guide Conduits for Precision Repair of Peripheral Nerve Defects. Issue 12 (18th February 2022) - Liu, Kai; Yan, Lesan; Li, Ruotao; Song, Zhiming; Ding, Jianxun; Liu, Bin; Chen, Xuesi
Abstract: The treatment of peripheral nerve defects has always been one of the most challenging clinical practices in neurosurgery. Currently, nerve autograft is the preferred treatment modality for peripheral nerve defects, while the therapy is constantly plagued by the limited donor, loss of donor function, formation of neuroma, nerve distortion or dislocation, and nerve diameter mismatch. To address these clinical issues, the emerged nerve guide conduits (NGCs) are expected to offer effective platforms to repair peripheral nerve defects, especially those with large or complex topological structures. Up to now, numerous technologies are developed for preparing diverse NGCs, such as solvent casting, gas foaming, phase separation, freeze‐drying, melt molding, electrospinning, and three‐dimensional (3D) printing. 3D printing shows great potential and advantages because it can quickly and accurately manufacture the required NGCs from various natural and synthetic materials. This review introduces the application of personalized 3D printed NGCs for the precision repair of peripheral nerve defects and predicts their future directions. Abstract : The personalized nerve guide conduits are quickly and accurately manufactured from various natural and synthetic materials by a three‐dimensional printing technique, which meets personalized imaging data to repair nerve defects of complex anatomical structures with the assistance of different growth factors and cells.